An experimental study of defect evolution in corners by autoclave processing of prepreg material. (May 2021) - Netzel, C.; Mordasini, A.; Schubert, J.; Allen, T.; Battley, M.; Hickey, C.M.D.; Hubert, P.; Bickerton, S.
Abstract: Autoclave prepreg processing is commonly used to produce high-quality structural components. Unlike in flat geometries, defects such as corner thickening, wrinkling and voids may be generated within complex structures during processing. This research investigates defect formation within the layup, debulking and consolidation stages of processing, focused on female moulded corners with high thickness to radius ratios. The influence of varying corner radii and proportion of 0°-fibres on the formation and size of corner defects was investigated. The wrinkling severity, corner thickening, and material flow behaviour of the samples was quantified through optical microscopy analysis. To characterise laminate corner-thickness variation following each processing step (layup, debulking, consolidation), a non-destructive laser measurement method was developed. It is demonstrated that corner thickening initially occurs during the layup and debulking process. Visualisation of the prepreg mass flow in corners shows that a higher 0°-fibres content increases the shear flow of the material during consolidation.